How to advocate for people who have problems with the law? A Book Review Communication in Legal Advocacy, Richard Ricke & Randall K. Stutman, South Carolina University Press - Arifin, Ridwan (Universitas Negeri Semarang, 2019)
Law faculty students are currently required to have abilities not only in terms of theoretical and scientific capacity, but also practice. Law faculty students in many conditions are also very much needed directly by the community in solving various problems faced by the community ranging from small and minor legal issues, to complex and complicated matters. The needs of the community for legal assistance and legal assistance have become unavoidable, especially in the midst of the development of information and technology flows and industry in the industrial revolution era 4.0.